Leveraging Blockchain Technology to Enhance Data Integrity and Transparency in Government Data Centers - Rotib, Adi Affandi; Windasari, Silviana; Bayu Bagaskoro; Ade Frihadi; Abdurohman, Abdurohman (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Abstract. Government data centers in Indonesia face significant challenges related to data integrity and transparency, impacting policy-making accuracy, operational efficiency, and public trust. Data fragmentation, information inconsistency, and vulnerability to manipulation and cyberattacks have become crucial issues. Blockchain technology, with its fundamental characteristics such as decentralization, immutability, cryptography, and consensus mechanisms, offers innovative solutions to address these problems. This research employs a systematic literature review and conceptual analysis approach to identify how blockchain principles can be effectively applied. The proposed conceptual model, which utilizes permissioned blockchains like Hyperledger Fabric and distributed storage systems such as the InterPlanetary File System (IPFS), demonstrates significant potential in creating a secure, transparent, and auditable data ecosystem. Blockchain implementation is expected to enhance data security, strengthen auditability, prevent fraud, improve operational efficiency, securely manage digital identities, and increase data availability and redundancy. Although implementation challenges exist, including technical complexity, immature regulations, costs, and human resource gaps, global case studies and initial initiatives in Indonesia indicate significant feasibility and benefits. This report recommends a holistic approach encompassing adaptive regulatory development, infrastructure and human resource investment, phased pilot projects, and multi-stakeholder collaboration to realize blockchain's full potential in improving government data governance. Keywords: Blockchain, Cybersecurity, Data Integrity, Data Transparency, Government Data Center